Answer:
y =
![(-mn)/(m-p^2)](https://img.qammunity.org/2021/formulas/mathematics/high-school/fiq60rtyup20nw2ywgfxez73le3nsxndm2.png)
Explanation:
Given
= p ( square both sides )
= p² ( multiply both sides by y )
m(y + n) = p²y ← distribute parenthesis on left side
my + mn = p²y ( subtract p²y from both sides )
my - p²y + mn = 0 ( subtract mn from both sides )
my - p²y = - mn ← factor out y from each term on the left side
y(m - p²) = - mn ← divide both sides by (m - p²)
y =
![(-mn)/(m-p^2)](https://img.qammunity.org/2021/formulas/mathematics/high-school/fiq60rtyup20nw2ywgfxez73le3nsxndm2.png)